Modelling the effect of oar shaft bending during the rowing stroke - Sliasas, A.; Tullis, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2011)
The behaviour of oar shaft bending during the drive phase is examined using a hydrodynamic-based model of the rowing stroke. By modelling the complex time-varying hydrodynamic load on the blade, the amount of shaft bending during the drive can be calculated. It is shown during the first 45 per cent of the drive that the blade rotation rate is up to 30 per cent slower than the oarlock rotation rate as the oar deflects and energy is stored in the flexible shaft. Through the remainder of the drive the shaft unbends, causing the blade to rotate up to 16 per cent quicker than the oarlock as the stored energy is transferred to the water and to shell propulsion. The effects that this bending has on oar blade and handle forces highlight the importance of accounting for oar shaft flexibility when modelling the rowing stroke.